Applying Digitization for improving Insurance business: a case study on Bajaj Allianz General Insurance Agent’s perception on role of digitization for band movement in Pune Region, Maharashtra - Dr. Priyanka Singh, Dr. Susil Kumar Sarangi (International Journal of Advanced Science and Technology, 2020)
This paper attempts to consider the view of General Insurance Agents on how digitalization impacts their general conduct after the presentation of digitalization. It additionally opens not many unopened premises of protection adventures with web of things which the operators should observe.